Interelasi Spiritualitas Jawa dan Hadis Nabi; Analisis Nilai-Nilai Hadis dalam Kidung ‎Wahyu Kolosebo - Fahimah, Rif'iyatul (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The assumption circulates that Javanese spirituality is not connected to the teachings of Islam due to its association with mystical, supernatural, superstitious, occult, and mythical practices. However, until today, Javanese spirituality influenced by Islam continues to be preserved, as reflected in one of the songs by Sri Narendra Kalasebo titled